Liposarcoma of the uterine corpus: A case report and literature review - Kaori Kiuchi; Kiyoshi Hasegawa; Shoko Ochiai; Nobuaki Kosaka; Hajime Kuroda; Yasushi Kaji; Ichio Fukasawa (Elsevier, 2018)
Liposarcoma of the uterine corpus is extremely rare. We performed a laparotomy on a 55-year-old woman with the complaints of abdominal distension and genital bleeding who was found to have a uterine tumor, 17 × 16 cm in diameter. The preoperative diagnosis was a lipoma or lipoleiomyoma of the uterine corpus. However, pathological examination revealed proliferation of mature adipocytes and lipoblast-like atypical cells with small, weakly pleomorphic nuclei and foamy or vacuolated cytoplasm present within a fibrous septum. Immunohistochemistry showed that the tumor cells were focally positive for mouse double minute 2 homolog (MDM2). The final pathological diagnosis was a well-differentiated liposarcoma of International Federation of Gynecology and Obstetrics (FIGO) stage IB (pT1bNxM0). On magnetic resonance imaging (MRI), T1 -weighted and fat-saturated images showed high and low intensity in the tumor, respectively, suggesting that this tumor contained a fat component. The septum inside the tumor had a contrast enhancement on T1-weighted, gadolinium-enhanced imaging. The septum was nonuniformly thickened and partially nodular. In hindsight, these findings may have suggested a well-differentiated liposarcoma in the uterine corpus rather than a lipoma or lipoleiomyoma. Clinicians should be aware of the possibility of a liposarcoma of the uterine corpus when a neoplasm contains adipose tissue and a nonuniformly thickened or partially nodular septum on MRI. Keywords: Liposarcoma, MDM2, MRI, uterine corpus, well-differentiated type